ANTIHYPERURICEMIC EFFECT OF RED GINGER POWDER AND LIME JUICE COMBINATION IN WISTAR RATS INDUCED HYPERURICEMIA - Eva Susanty Purba; Chikita Dian Rahma Saphira; Salma Yasmine Azzahara; Edwin Basyar; Muflihatul Muniroh; Ainun Rahmasari Gumay (Jurnal Kedokteran Diponegoro)
Background: Hyperuricemia is an abnormally high level of uric acid in the blood. Ginger and lime are natural ingredients that contain antioxidants and anti-inflammatory which could reduce blood uric acid levels. This study aims to prove the effect of red ginger powder and lime juice combination on uric acid levels of Wistar rats induced hyperuricemia.